Structure and function meet at the nicotinic acetylcholine receptor-lipid interface - Barrantes, Francisco José (2023)
Fil: Barrantes, Francisco José. Pontificia Universidad Católica Argentina. Instituto de Investigaciones Biomédicas. Laboratorio de Neurobiología Molecular; Argentina